Economic burden of non-communicable diseases on households in Nigeria: evidence from the Nigeria living standard survey 2018-19 - Adelakun Odunyemi; Taslima Rahman; Khurshid Alam (BMC, 2023)
Abstract Background The importance of non-communicable diseases (NCDs) in Nigeria is reflected in their growing burden that is fast overtaking that of infectious diseases. As most NCD care is paid for through out-of-pocket (OOP) expenses, and NCDs tend to cause substantial income losses through chronic disabilities, the rising NCD-related health burden may also be economically detrimental. Given the lack of updated national-level evidence on the economic burden of NCDs in Nigeria, this study aims to produce new evidence on the extent of financial hardship experienced by households with NCDs in Nigeria due to OOP expenditure and productivity loss. Methods This study analysed cross-sectional data from the most recent round (2018-19) of the Nigeria Living Standard Survey (NLSS). Household-level health and consumption data were used to estimate catastrophic health expenditure (CHE) and impoverishing effects due to OOP health spending, using a more equitable method recently developed by the World Health Organization European region in 2018. The productivity loss by individuals with NCDs was also estimated from income and work-time loss data, applying the input-based human capital approach. Results On average, a household with NCDs spent ₦ 122,313.60 or $ 398.52 per year on NCD care, representing 24% of household food expenditure. The study found that OOP on cancer treatment, mental problems, and renal diseases significantly contribute to the cost of NCD care. The OOP expenditure led to catastrophic and impoverishing outcomes for households. The estimations showed that about 30% of households with NCDs experienced CHE in 2018, using the WHO Europe method at the 40% threshold. The study also found that the cost of NCD medications was a significant driver of CHE among NCD-affected households. The results showed heterogeneity in CHE and impoverishment across states and geographical regions in Nigeria, with a higher concentration in rural and North East geopolitical locations. The study also found that 20% of NCD-affected households were impoverished or further impoverished by OOP payment, and another 10% were on the verge of impoverishment. The results showed a negligible rate of unmet needs among households with NCDs. Conclusions The study highlights the significant effect of NCDs on Nigerian households and the need for effective policy interventions to address this challenge, particularly among the poor and vulnerable.